Evolution of household food availability in the municipality of São Paulo from 1979 to 1999 - Moreira CLARO, Rafael (2023)
ObjectiveFood budget surveys data were analyzed in order to describe the evolution (1971-1999) of food and nutrient availability in São Paulo, Brazil. MethodsThe study uses data from two Family Budget Surveys conducted by Fundação Instituto de Pesquisas Econômicas, carried out during the periods of 1971-1972 (2,380 households) and 1998-1999 (2.351 households) in the urban area of São Paulo city. Per capita daily food availability was estimated by calculating the fraction of all the food bought for the month attributed to each participant of this study divided by the number of days in the month. The food patterns of this population were characterized according to the caloric and nutrient distribution of the 18 food groups and nutrients obtained in the respective surveys. ResultsThe results show increased consumption of meats, dairy, processed foods and chilled and frozen meals. On the other hand, the consumption of grains, fruits and vegetables decreased. The consumption of sugar, oils and fats reduced slightly but since the consumption of processed foods increased, it is not possible to say that diet quality improved. At the same time the consumption of proteins, fats and calcium increased while the consumption of carbohydrates, fiber, folate and vitamin C decreased. ConclusionThe changes in the eating patterns of the population of São Paulo are consistent with the growing prevalence of obesity and non-communicable chronic diseases observed in the city.